Influência de íons metálicos na estrutura de substâncias húmicas detectados por espectroscopia - Barriquello, Marcilene Ferrari (Universidade Federal de São Carlos, 2005)
INFLUENCE OF METAL CATIONS IN THE STRUCTURE OF HUMIC SUBSTANCES AS DETECTED BY SPECTROSCOPY, involves a study by which starting from precursors of humic substances, some polymers were obtained, characterized and comparable with samples of humic acids. One such polymer with similar characteristics with humic acids was obtained by using as precursors hydroquinone, p-benzoquinone and 4-aminbenzoic acid, subjected to a synthesis under polymeric oxidation at an alkaline medium. The following structural characteristics of such polymers were studied in comparison with humic acids: influence of Cu, Fe and Mn cations in the structure of the synthesized polymers by spectral characteristica of Fourier Transform Infrared Spectroscopic (FTIR), absorbance with UV-Vis light, fluorescence; experiments with Size Exclusion Chromatography (SEC) and Atomic Force Microscopy (AFM) with the polymers and humic acids. It has been found that the complexation with the Cu, Fe and Mn cations has affected the structure by increasing the molecular size as observed by the Size Exclusion Chromatography. After complexation with the metal cations the FTIR, UV-Vis and Fluorescence spectra has shown significant changes due to structural modifications, which indicates complex formation specially with the carboxylic and phenol groups found in the obtained polymers.
Influence of metal cations in the structure of humic substances as detected by spectroscopy
Keywords: Química analítica; Métodos espectroscópicos; Cromatografia; Íons metálicos; Substâncias húmicas; Ácido húmico sintético; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA